2014
DOI: 10.4236/ns.2014.611086
|View full text |Cite
|
Sign up to set email alerts
|

Radon Concentrations Measurement in Aljouf, Saudi Arabia Using Active Detecting Method

Abstract: Rn-222 is the most important source of natural radiation and is responsible for approximately half of the received dose from all sources. Most of this dose is from inhalation of the Rn-222 progeny, especially in closed ares. Portable alpha particle detector, RAD7 was used for Rn-222 measurements inside the main campus of Aljouf University at Saudi Arabia in order to estimate the effective dose to the occupants from 222 Rn and its progeny. The values of annual effective doses for radon inhalation by the inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…On the other hand, the present results showed that the measured concentration values of 222 Rn in Al-Kharj city are compatible with those measured in some other countries. Also, our result (19.23 Bq/m 3 ) is in a consistent with the other studies in Saudi Arabia (Abuelhia, 2017;Alenezy, 2014;Alghamdi & Aleissa, 2014;Alghamdi, Aleissa, & Al-Hamarneh, 2019;El-Taher et al, 2013;Mona, Al-Jarallah, & Rehman, 2005). It is observed that no average radon concentration is above the action levels that are recommended by ICRP (ICRP, 2010).…”
Section: Comparison With Studies In Saudi Arabia and Other Countriessupporting
confidence: 93%
“…On the other hand, the present results showed that the measured concentration values of 222 Rn in Al-Kharj city are compatible with those measured in some other countries. Also, our result (19.23 Bq/m 3 ) is in a consistent with the other studies in Saudi Arabia (Abuelhia, 2017;Alenezy, 2014;Alghamdi & Aleissa, 2014;Alghamdi, Aleissa, & Al-Hamarneh, 2019;El-Taher et al, 2013;Mona, Al-Jarallah, & Rehman, 2005). It is observed that no average radon concentration is above the action levels that are recommended by ICRP (ICRP, 2010).…”
Section: Comparison With Studies In Saudi Arabia and Other Countriessupporting
confidence: 93%
“…On the other hand, there have been some small studies using active devices (mostly RAD7). For example, at Aljouf University, several offices were surveyed, and there was an average value of 12 Bq m −3 [136]. Abuelhia [137] reported an average radon concentration level of 19 Bq m −3 in apartments located in the city of Dammam (Eastern Province).…”
Section: Saudi Arabia (V)mentioning
confidence: 99%
“…The interior of the RAD-7 instrument contains a hemisphere of 0.7 l volume with an ion-implanted silicon solid-state 𝛼 −detector, and an air pump to be found at the centre. A representation of the measurement chamber with the detector is shown in Figure 2 [14]. The high voltage power circuit charges the inside conductor to a potential of 2 000 to 2 500 V, creating an electric field throughout the volume of the detector [15].…”
Section: Alpha-spectrometry Using Solid-state Alpha Detectorsmentioning
confidence: 99%